Attributing the spatial-temporal contributions of inflow nitrogen and phosphorus loads to lake water quality and insights for effective mitigation strategies - Zhilong Zhao; Bo Yao; Yu Li; Zhaokui Ni; Shengrui Wang (Journal of Hydrology: Regional Studies, 2025)
Study region: Erhai Lake, a typical plateau lake in China. Study focus: Inflow nitrogen and phosphorus loads (INPL) impair lake water quality, while an in-depth understanding of their contributions to lake water quality represents a major obstacle to formulating effective INPL mitigation strategies. This study leveraged a three-dimensional hydrodynamic model to examine the spatial-temporal influence of INPL on the water quality of Erhai Lake and to determine reduction priorities. New hydrological insights for the region: The INPL contributions showed strong spatial-temporal heterogeneity, with spatial contributions primarily from the Xiaguan Area (24.06 %–35.47 %), Miju Area (16.90 %–22.96 %), and Yinqiao–Wanqiao Area (11.16 %–20.28 %) and temporal contributions primarily from June to September (68.25 %–75.59 % of the total). Key factors affecting INPL contributions were inflow volume, built-up land area, cropland area, slope, precipitation and air temperature. A 70 % reduction in INPL reduced total nitrogen, total phosphorus, and chlorophyll a by 14.56–42.39 %, indicating that merely reducing INPL was insufficient to achieve immediate improvements in water quality. The effect of reducing inflow total phosphorus load (IPL) on chlorophyll a was 1.82 times greater than that of reducing inflow total nitrogen load (INL), suggesting that IPL reduction is more effective in controlling algal blooms. To achieve mild and moderate algal bloom targets, IPL should be reduced by 48.69 % (38.37 tons) and 38.91 % (30.67 tons). The Xiaguan Area and June were the most critical for IPL reduction.